A Statistical Study on Microorganisms that Cause Tooth Decay and Prevention and Treatment Methods - Widad sameer jaaz1, Ohood Salman Jawad2, Hassanain Jwad Abid Al Hussein1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current research includes knowledge of the effect of microbes on dental caries, by providing the environment suitable for the growth of bacteria and fungi that cause this decomposition, fermentation and decay and thus erode the texture of the tooth and then full tooth decay. These are the macrophages that lead to tooth decay (streptococcus species, Staphylococcus aureus, Candida, Lactobacillus, Actinomycosis, Micrococcus, Antibacterials, Bacillus, Actinobacillus) in different percentages: 33.3%, 21.3%, 14.7%, 12.1%, 8.2 , 4.5%, 3.4%, 1.3%, 1.2%), respectively. There are many other factors that help tooth decay occur: the host (tooth and saliva), microorganisms in the form of tooth plaque, substrate (diet).